Originally Posted by

**mvho** If $\displaystyle V=(6-\frac{\pi^2}{3})*h$ and $\displaystyle \frac{h}{2-r}$ =$\displaystyle \frac{5}{2}$

Write V as a function of "h". Simplify the function so you can express it as a polynomial in "h".

My Answer: I solved for r first and plugged in R in the original equation where v=(6-etc...). I solved for R in the equation: h/2-r=5/2 which I found as: 4h^2-40h+100/75=r^2.

My algebra is not the best so if you catch any mistakes let me know!

Answer (I think): (4*h^3/75) + (40*h^2)+350h

TIA